Priložnostni spolni odnosi z vidika psihologije: intrapersonalni in situacijski dejavniki - Černilec, Maša (Anthropos (Ljubljana), 2022)
Casual sexual relationships (csrs) are a widespread phe- nomenon, involving mainly adolescents and emerging adults. In this paper, we present several factors that are associated with csrs. We touch upon individual differences in sexual behaviour and motives for participating in csrs. We establish that csrs are a part of a broader social context, define the term hookup culture and present some of the characteristic situations and scripts that predict csrs. We empha- size psychological consequences of csrs, more specifically emotional responses to csrs and their connection with mental health and well- being. We suggest that the psychological aspect of casual sex should be given as much attention in education as the health aspect.
Keywords: casual sex; casual sexual relationships; hookup culture; individual differences; intimna srečanja; priložnostni spolni odnosi; psihologija; psihološke posledice; psychological consequences; psychology; sexuality; spolnost